Screening for cervical dysplasia and reproductive tract infections among coffee plantation workers in Kodagu District, Karnataka, India. - Ramesh, Naveen; Dhanpal, Nihkil; Victor, Thaddeau; Nisha, Cathrin (International Journal of Occupational Safety and Health, 2016)
Background: Cervical dysplasia is a pre malignant condition and cervical cancer is a leading cause of death among women in developing countries. This study was undertaken to coffee plantation workers to assess the prevalence of cervical dysplasia and reproductive tract infections (RTI) and its associated ethological factors among women aged 40 years and above. Methods: It was a cross sectional study conducted among female plantation workers aged 40 years and above and employed in coffee estates in Kodagu District, Karnataka, India. The tools in this study included an interview schedule to help collect socio demographic details and the procedures included per vaginal and per speculum examination along with Pap smear test. Results: A total of 141 women aged 40 years and above were screened for cervical dysplasia and reproductive tract infections. The prevalence of cervical dysplasia on Pap smear was seven percent and that of RTI was 12.05%. In this study there was no statistically significant association between cervical dysplasia or RTI with socio demographic variables like age, education, per capita in-come, age at marriage, age at first pregnancy or number of children. Conclusion: The prevalence of cervical dysplasia on Pap smear was seven percent and that of RTI was 12.05%. Regular screening of women in the reproductive age group with Pap smear and prevention and treatment of both partners with RTI may help reduce the chances of developing cervical cancer. International Journal of Occupational Safety and Health, Vol 4 No 2 (2014) 01 – 04